The Relationship Between CRP Level and Age in Salmonella Typhi Patient - Haider Abdul-Moneem Al-Mothafer (Journal La Lifesci, 2026)
Typhoid fever has increased in some populations, hence the current study, aimed to evaluate the prevalence of salmonella seropositivity and other relevant factors such as sex, age, and CRP positivity among febrile patients, especially among the patients estimated to be suffering with typhoid fever located at Al-Najaf province in Iraq. The study comprised 79 febrile patients who presented for intestinal complaints at Al-Hakeem General Hospital, AL Sajad Hospital, and AL Najaf Hospital’s serological departments within Al-Najaf province between October 2024 and January 2025. Those were between 1 and 75 years of age. This study employed rapid testing modalities for the qualitative detection of typhoid infection and assessment of serum CRP levels. Among the 79 febrile patients screened, 41 (51.9%) were female, 38 male (48.1%) was assessed. On typhoid seropositivity, 23 individuals (29.2%) tested positive, and 56 (70.8%) negative, but no differences between gender were found (P=0.36). Age distribution of febrile patients was further classified into 5 groups, 1-15 years, 16-30 years, 31-45 years, 46-60 years, 61-75 years. Notably, the greatest prevalence occurred at a range of 1 to 15 years of age (27.8%), then in the 16-30 year group (25.3%). Among those diagnosed as positive for Salmonella seropositivity, it was reported that those ages 61-75 had a higher positivity rate of 12.7%, indicating a statistically significant difference (P=0.001).